Nahum, Habakkuk, Zephaniah - Patterson, Richard Duane (Chicago, IL Moody, 1991)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Nahum -- commentaries; Bible. O.T. Habakkuk -- commentaries; Bible. O.T. Zephaniah -- commentaries